Situação da cisticercose bovina no Brasil - Marques Rossi, Gabriel Augusto [UNESP]; Rodomilli Grisolio, Ana Paula [UNESP]; Prata, Luiz Francisco [UNESP]; Buerger, Karina Paes [UNESP]; Lux Hoppe, Estevam Guilherme [UNESP] (Univ Estadual Londrina, 2014)
The taeniasis-cysticercosis complex is a long known zoonotic parasitosis characteristic of underdeveloped countries. In addition to its public health significance, this parasitosis is cause of economic losses to the beef production chain, and synonymous of technical inadequacy in relation to the adoption of Good Agricultural Practices. The occurrences of both human teniasis and bovine cysticercosis could and should be controlled with basic sanitary measures. However, there is much variation in the occurrence of the disease in cattle, characterizing a low rate of technical development as well as problems related to the adoption of basic sanitation measures. This review describes, in details, the causative agent and its epidemiological chain, besides raising current information about the occurrence of bovine cysticercosis in different regions of Brazil, aiming at the adoption of prophylactic measures by different segments responsible.
Bovine cysticercosis situation in Brazil
Keywords: Cysticercosis; cattle; sanitary inspection; meat